Dialogismo e tradição nas histórias em quadrinhos contemporâneas - Figueira, Diego Aparecido Alves Gomes (2009)
This study aims to examine some aesthetic trends from super-heroes comic books relate to the activity of collect them. The narratives of these magazines have long and continuous stories, without an end in perspective, interconnected with others magazines of the same publisher. The collector-reader appears crucial to examine the comic book production, since its plots usually are based on evidence and information about the characters mostly recovered of other older stories. We also consider relevant the presence of a media segment specialized in comics, also responsible for a form of criticism of comics that results in the idea of a canon and an aesthetic tradition to the genre. That specialized media became the space where rises and circulates a discourse about comics and a fan knowledge that dialogue with the discourse of the narratives. Based on Mikhail Bakhtin´s linguistics studies, we try to comprehend how that dialogue results in some sophisticated works, where the discourse about comics appears as metalanguage. One of that works is the Darwyn Cooke and Dave Stevens s graphic novel DC: The New Frontier, our principal object of analysis in this study.